Seed quality assessment of three photo-insensitive cultivars of lablab bean influenced by date of sowing - Alam, KM Kabir; Bhuiyan, MKR; Halim, GMA; Zakaria, M; Hossain, MJ (Bangladesh Journal of Agricultural Research, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Quality of seeds of three cultivars (IPSA Seem-2, BU Seem-3 and IPSA Seem-5) of lablab bean (Lablab purpureus L. Sweet) collected from crops planted in three different dates (15 May, 15 July, and 15 September 2003) was assessed in respect of different parameters. The maximum percentage of seeds of cv. IPSA Seem-2 was germinated (95.67) whereas, BU Seem-3 had the maximum electrical conductivity (EC) (316.06 Î¼s/cm) followed by IPSA Seem-5 (261.53 Î¼s/cm). The cv. IPSA Seem-2 also had the highest vigour index (VI) (65.04) and coefficient of germination (CG) (58.90). The maximum length of root and shoot was 13.73 cm and 12.98 cm in IPSA Seem-5 and IPSA Seem-2, respectively. The percentage of dry matter of root and shoot was the highest for BU Seem-3 (23.68 and 12.15, respectively), whereas, the composite sample of root and shoot of IPSA Seem-2 had the highest value of dry matter (14.54%). Seeds of September planted crops had better germination percentage (95.67), VI (50.07), CG (47.65), length of root (13.63 cm), dry matter of root (24.79%), shoot (13.34%) and composite sample (15.14%). Whereas, seeds of May planted crops had the maximum EC (388.23 Î¼s/cm) and length of shoot (15.29 cm). Seeds of cv. IPSA Seem-2 collected from September planted crops had the maximum germination percentage (97.75), VI (70.96), CG (64.13), length of shoot (11.41 cm) and dry matter percentage of composite sample of root and shoot (16.58). BU Seem-3 of May planted crops had the maximum EC (469.78 Î¼s/cm). But BU Seem-3 of September planting had the highest dry matter of root of seedling (25.19%). Seedlings of cv. IPSA Seem-5 planted in September had the highest length of roots (14.63 cm) and dry matter of shoot (13.79%). Key Words: Seed quality, photo-insensitive, dates of planting and lablab bean. doi:10.3329/bjar.v33i3.1597 Bangladesh J. Agril. Res. 33(3) : 381-389, September 2008